Analysis of the Influence of Organizational Justice on Job Satisfaction with Organizational Trust as a Mediating Variable for Employees of Construction Companies - Siregar, Dewi Ratna Bulan; Nasution, Zulkarnain (Indonesia Auditing Research Journal, 2024)
This study aims to analyze the effect of organizational justice on employee job satisfaction, with organizational trust as a mediating variable. The results show that organizational justice has a significant direct effect on employee job satisfaction and organizational trust. Organizational trust was also found to have a significant direct effect on employee job satisfaction. However, the indirect effect of organizational justice on job satisfaction through organizational trust is not significant. These findings indicate that organizational justice plays an important role in enhancing employee job satisfaction, but organizational trust does not mediate this relationship. The practical implication of this research is the need for organizations to pay attention to the aspect of justice in decision-making processes, reward distribution, and interpersonal interactions to improve employee job satisfaction .